Digital Dilemmas : The State, the Individual, and Digital Media in Cuba - Venegas, Cristina, 1959- (Book collections on Project MUSE., 2010)
Digital Dilemmas views Cuba from the Soviet Union's demise to the present, to assess how conflicts over media access play out in their both liberating and repressive potential. Drawing on extensive scholarship and interviews, Cristina Venegas questions myths of how Internet use necessarily fosters global democracy and reveals the impact of new technologies on the country's governance and culture, including film in the context of broader media history, as well as artistic practices such as digital art and networks of diasporic communities connected by the Web.